(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
Automated student seat allocation is a computerized process that utilizes algorithms to assign seats to students in educational institutions. This study provides an overview of automated student seat allocation, highlighting its benefits and challenges. We discussed the working mechanism of automated seat allocation systems, factors considered during the allocation process, and the algorithms employed to optimize the process. We emphasized the advantages of automated systems, such as speed, accuracy, and fairness, over traditional manual allocation methods. The study also addresses implementation challenges, including data privacy concerns and the importance of personnel training. The study developed a software using three programming stacks, each with its own unique function. The front-end is developed using React JS, the back-end utilizes Django, and the main software interface was built using Python programming language. Exam details are stored in the database held by the back-end and are presented to students through the front-end after they input their registration number and examination course code. By emphasizing the significance of automated student seat allocation systems, we underscored their role in ensuring a fair and efficient seat allocation process in educational institutions.